Penurunan Kadar COD (Chemical Oxygen Demand) Air Sungai Cisadane Menggunakan Metode Fenton - Adelina, Dina; Indrawati, Wiwik; Filosa, Aminudin; Hakim, Rusnia Junisa; S, Agustina Dyah; Ismet, Rhahmasari; Yullia, Nuke; Lita, Nurul (Politeknik Negeri Lhokseumawe, 2026)
The Cisadane River is one of the main water resources in Tangerang and surrounding areas. However, its water quality has declined due to domestic and industrial pollution, which increases the Chemical Oxygen Demand (COD) level. This study aimed to evaluate the effectiveness of the Fenton method in reducing COD levels in Cisadane River water and to determine the optimum reaction time for the treatment process. The experiment was conducted using 100 mL of river water sample treated with Fenton reagent consisting of FeSO₄ 0.3 M and H₂O₂ 0.8 M. The treatment was carried out at reaction times of 60, 120, 180, and 240 minutes, and COD levels were analyzed using a photometer. The results showed that the initial COD concentration of 495 mg/L decreased to 290 mg/L after 60 minutes, 195 mg/L after 120 minutes, 145 mg/L after 180 minutes, and 95 mg/L after 240 minutes. The highest COD removal efficiency was achieved at 240 minutes, with a reduction of 80.81%, and the final COD concentration met the domestic wastewater quality standard of 100 mg/L. In conclusion, the Fenton method was effective in reducing COD levels in Cisadane River water, with the optimum treatment time obtained at 240 minutes.